The effect of MnCO3 on the gain coefficient for the 4I13/2 / 4I15/2 transition of Er3+ ions and nearinfrared emission bandwidth flatness of Er3+/Tm3+/Yb3+ co-doped barium zinc silicate glasses† - Nguyễn, Đình Trung (2024)
The roles of Mn2+ ions in the MnCO3 compound, leading to the formation of an Mn2+–Yb3+ dimer and affecting the gain coefficient for the 4I 13/2 / 4I 15/2 transition of Er3+ ions and near-infrared (NIR) emission bandwidth flatness of Er3+/Tm3+/Yb3+ co-doped in SiO2–ZnO–BaO (SZB) barium zinc silicate glasses, were investigated in this work. The composition of all elements from the original raw materials that exist in the host glasses was determined using energy-dispersive X-ray spectroscopy (EDS). Under the excitation of a 980 nm laser diode (LD), the NIR emission of Er3+/Tm3+/Yb3+-co-doped SZB glasses produced a bandwidth of about 430 nm covering the O, E, and C bands. The effects of Mn2+ ions and the Mn2+–Yb3+ dimer on the gain coefficient for the 4I 13/2 / 4I 15/2 transition of Er3+ ions and bandwidth flatness of NIR emission of Er3+/Tm3+-co-doped and Er3+/Tm3+/Yb3+-co-doped SZB glasses were also assigned. The optimal molar concentration of Mn2+ ions was determined such that the NIR bandwidth flatness of Er3+/Tm3+/Yb3+-co-doped SZB glasses was the flattest. In addition, the role of Mn2+ ions in reducing the gain coefficient for the 4I 13/2 / 4I 15/2 transition of Er3+ ions was also calculated and discussed.